SUHU GAS BUANG MESIN DIESEL KAPAL PERIKANAN DENGAN BIOFUEL. - Muchtar Ahmad (Program Pascasarjana Universitas Riau, 2007)
Gas emission and temperature as result of fuel used in diesel engine of a fishing boat were ineasu red, in order to know its impact on fisherman comfortness as well as also can use to understand its share in global wartning or climate change. The temperature of emission gas of solar is stable increase proportional top the engine round (rpm). it is similar with mixture biofuel but the increase rate of emission gas of tile mixture biofuel rather low, even the gas emission temperature of 65% biofuel+35% solar tincture decrease as engine round (rpm) increasing. Similarly to the water cooler temperature of engine, but almost stable specially during the engine round of 500rpm to 2200 rpm. it shows that engine water cooler effectively absorp the engine temperature so that the temperature of engine tend to decrease as it indicates by the temperature of oh. Generally the oh temperature decrease as the engine round increase, as it is a reflection of engine temperature too. The emission gas of biofuel+ solar mixture from exhaust pipe almost without color and no aroma, while the color of solar fuel deeply black with uncomfort smelly. The emission gas of biofuel+ solar mixture from exhaust pipe almost without color and no aroma, while the color of solar fuel deeply black with uncomfort smell.